The Aspergillus fumigatus conidial melanin production is regulated by the bifunctional bHLH DevR and MADS‐box RlmA transcription factors. Issue 2 (28th July 2016) - Valiante, Vito; Baldin, Clara; Hortschansky, Peter; Jain, Radhika; Thywißen, Andreas; Straßburger, Maria; Shelest, Ekaterina; Heinekamp, Thorsten; Brakhage, Axel A.
Summary: Melanins play a crucial role in defending organisms against external stressors. In several pathogenic fungi, including the human pathogen Aspergillus fumigatus, melanin production was shown to contribute to virulence. A. fumigatus produces two different types of melanins, i.e., pyomelanin and dihydroxynaphthalene (DHN)‐melanin. DHN‐melanin forms the gray‐green pigment characteristic for conidia, playing an important role in immune evasion of conidia and thus for fungal virulence. The DHN‐melanin biosynthesis pathway is encoded by six genes organized in a cluster with the polyketide synthase gene pksP as a core element. Here, cross‐species promoter analysis identified specific DNA binding sites in the DHN‐melanin biosynthesis genes pksP ‐ arp1 intergenic region that can be recognized by bHLH and MADS‐box transcriptional regulators. Independent deletion of two genes coding for the transcription factors DevR (bHLH) and RlmA (MADS‐box) interfered with sporulation and reduced the expression of the DHN‐melanin gene cluster. In vitro and in vivo experiments proved that these transcription factors cooperatively regulate pksP expression acting both as repressors and activators in a mutually exclusive manner. The dual role executed by each regulator depends on specific DNA motifs recognized in the pksP promoter region. Abstract : The promoter region present in the DHN‐melanin cluster can be specifically recognized by two transcriptional regulators belonging to the bHLH (DevR) and MADS‐box MEF2‐like (RlmA) families. In vitro and in vivo experiments proved that these transcription factors cooperatively regulate DHN‐melanin gene expression acting both as repressors and activators in a mutually exclusive manner. In addition, the dual role executed by these regulators depends on specific DNA motifs recognized in promoter regions.